(untitled) (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2026)
This study aims to analyze the effect of service quality and discounts on customer satisfaction at Freshindo Cabang Gatsu Tengah by Tiara Dewata. The research is located at Freshindo Cabang Gatsu Tengah by Tiara Dewata, located at Jl. Gatot Subroto No.314, Tonja, North Denpasar District, where this study uses a quantitative research method with a total sample of 110 respondents who are consumers of Freshindo Cabang Gatsu Tengah by Tiara Dewata. The criteria determined by the researcher are that they must be consumers of Freshindo Cabang Gatsu Tengah by Tiara Dewata, have a transaction history at Freshindo Cabang Gatsu Tengah by Tiara Dewata, and be consumers who already have a Tiara Group membership card. The data collection methods in this study were observation, interviews, documentation, and questionnaires. The testing was conducted using research instrument tests, classical assumption tests, with data analysis techniques including multiple linear regression analysis, determination analysis, partial tests (t-test), and simultaneous tests (F-test). The conclusion of this study is that Service Quality has a positive and significant effect on customer satisfaction at Freshindo Cabang Tengah by Tiara Dewata, thus the first hypothesis is accepted. Discounts have a positive and significant effect on customer satisfaction at Freshindo Cabang Tengah by Tiara Dewata, hence the second hypothesis is accepted. The quality of service and discounts simultaneously affect customer satisfaction at Freshindo Central Branch by Tiara Dewata, thus the third hypothesis is accepted.